Community Participation in Indonesia in Preservation and Continuation of Environmental Protection and Management - SILAM, Achmad Adi Surya Guntur; KRISTHY, Mutia Evi; SIBOT, Yesieari Silvanny; HALIM, Suriansyah (Protection: Journal Of Land And Environmental Law, 2025)
The concept of sustainable development, as discussed at the United Nations Conference on the Environment in Stockholm in 1972, focuses on development that considers environmental impacts. It highlights the constitutional mandate in Article 28H of the 1945 Constitution of the Republic of Indonesia, emphasizing the right of every Indonesian citizen to a good and healthy living environment. Despite this constitutional provision, implementing sustainable development has faced challenges and confusion at the policy and regulatory levels. In Indonesia, where forest and land fires are recurrent disasters with severe ecological, economic, and social consequences, the aims underscore the significance of environmental awareness and proactive measures in addressing these issues. It emphasizes the interdependence between human actions and the environment and calls for responsible environmental stewardship. The research method used is legal research, which departs from statutory provisions, namely research on the legal principles of environmental provisions, specifically regarding community participation in environmental management. Overall, this provides insights into the critical role of environmental awareness and sustainable development in ensuring a better future for Indonesia's environment and its citizens, in alignment with constitutional mandates and international principles.